Pengaruh Sikap Higiene Tidur Terhadap Kejadian Insomnia Pada Mahasiswa Universitas Mulawarman - Adheya Putrindashafa; Denny J. Rotinsulu; Ika Fikriah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Insomnia is difficulty starting or maintaining sleep. There are several factors that are considered to be able to trigger and perpetuate insomnia, one of which is the sleep hygiene, which is included in the moderation factor. However, there is some controversy regarding the involvement of insufficient sleep hygiene towards insomnia. This study aims to determine the effect of sleep hygiene attitudes on the incidence of insomnia and a description of the incidence of insomnia and sleep hygiene in Mulawarman University students. The design of this study was observational analytic with a cross-sectional method, which consisted of 140 Mulawarman University students from 14 faculties. The sampling technique used is consecutive sampling. The data taken is primary data in 14 faculties of Mulawarman University. The research instrument used was the Insomnia Rating Scale questionnaire from the Kelompok Studi Psikiatri Biologi Jakarta and the Sleep Hygiene Index. The results of the study used the Chi-Square test and the Kolmogorov-Smirnov test obtained p value> 0.005. Based on the degree of insomnia, found 65% of respondents suffer from mild insomnia. The frequency of the sexes of women who suffer from insomnia more than men. Based on the degree of sleep hygiene attitudes, it was found that 78.6% of respondents had moderate sleep hygiene attitudes. This study concluded that there was no effect of sleep hygiene attitudes on the incidence of insomnia in Mulawarman University students.